The diagnostic value of next-generation sequencing technology in sepsis - Cao, Xiao-guang; Zhou, Shu-sheng; Wang, Chun-yan; Jin, Kui; Meng, Hua-dong (Frontiers in Cellular and Infection Microbiology, 2022)
Objective This study aims to assess the clinical utility of next-generation sequencing (NGS) in sepsis diagnosis. Methods A prospective study was conducted on patients with a high suspicion of sepsis by unknown pathogens from January 2017 to December 2021. Blood samples were taken from patients to perform NGS, blood culture (BC), leucocyte (WBC), procalcitonin (PCT), creatinine (CREA), Albumin (ALB) and C-reactive protein (CRP) tests. Results The feedback time for BC was 3 5 days for bacteria and 5 7 days for fungi, while the turnover time for NGS was only 24 h. The clinical diagnosis was considered the “gold standard”. 83 patients passed our inclusion criteria and were separated into two groups by clinical diagnosis. 62 met the clinical diagnosis criteria for sepsis and 21 were non-sepsis. The data from the two groups were retrospectively compared and analyzed. Of 62 sepsis in 83 patients, 8(9.64%) were diagnosed by both BC and NGS, 51 (61.45%) by NGS only, 1(1.20%) by BC and 2 (2.41%) by conventional testing only; PCT, CREA, CRP levels and the detection rate of NGS and BC were higher in the sepsis group than in the non-sepsis group, while ALB levels were lower (p<0.05). The logistic regression results in our study revealed that NGS and ALB were independent prediction factors for sepsis (p<0.05), the area under the receiver operating characteristic curve (AUC), sensitivity and specificity of NGS for diagnosing sepsis was 0.857, 95.16% and 76.19%, while ALB was 0.728, 58.06%, 80.95%, respectively. The combination’s sensitivity, specificity and AUC of NGS and ALB were 93.55%, 85.71% and 0.935, greater than that of Albumin or NGS only (both p<0.05). Conclusion NGS can effectively and quickly identify pathogens, thereby emerges as a promising technology for sepsis diagnosis. Combination of NGS and ALB can be used for early screening and is more powerful than NGS or ALB only.